Takut Akan Tuhan Sebagai Dasar Hidup Kaum Muda: Telaah Amsal 1:7 dalam Konteks Milenial dan Gen Z: I. Latar Bekalang Kitab Amsal - Krisna Sianturi; Gregorius Tri Wardoyo; Benny Phang Khong Wing (Sekolah Tinggi Widya Sasana, 2025)
Millennials and Gen Z live in an era characterized by technological advances, rapid information flow, and shifting social and spiritual values. In the midst of this reality, they face serious challenges in shaping a meaningful life that is morally and spiritually rooted. Moral relativism, individualism, and secularism have become dominant characteristics that erode submission to divine authority, and cause many young people to experience value confusion, spiritual emptiness, and a crisis of meaning in life. In this context, Proverbs 1:7